Dolutegravir-based anti-retroviral therapy is effective and safe in HIV–infected paediatric patients - Eugenia Bruzzese (Italian Journal of Pediatrics, 2018)
Abstract Background Treatment of HIV infection in adolescents is challenging due to long duration of therapy and poor adherence. Recently, the integrase strand transfer inhibitor dolutegravir (DTG) has been approved for the use in adolescents with HIV, but evidence in clinical practice is very limited. Methods We describe six cases of HIV-infected children/adolescents successfully treated with DTG-based regimen. Data relative to children/adolescents managed at the Referral Center for Pediatric HIV/AIDS of the University of Naples were reviewed. Patients were tested before introduction of DTG, after 1 month and every 3 months in the first 2 years to assess virologic and immunological response, tolerance and development of side effects. Families were asked to report any suspected adverse events. Results Six patients (2 male, median age 17 years, range 12–18) were started on DTG-based anti-retroviral regimen due to low adherence to anti-retroviral treatment (ART), multiple drug resistance mutations, or development of ART-related side effects. Within 4–8 weeks after DTG treatment onset, a complete viral suppression and a concomitant increase of CD4+ cell count was observed. Four patients showed a persistent suppression after 2 years of follow-up, and 2 patients at about 1 year. One month after the introduction of DTG, the patient enrolled because of severe dyslipidaemia and hyper-transaminasemia showed a complete normalization of laboratory values. During follow-up (median 24 months, range 9–24) no adverse events were reported and most patients demonstrated a good adherence to treatment. Conclusions DTG-based treatments demonstrated efficacy and good safety profile in adolescents. All patients demonstrated a rapid virologic and immunological response within 4–8 weeks, with good adherence and absence of side effects.